Simulation of anthropogenic aerosols mass distributions and analysing their direct and semi‐direct effects over South Africa using RegCM4. (13th December 2014) - Tesfaye, M.; Sivakumar, V.; Botai, J.; Tsidu, G. Mengistu; Rautenbach, C. J. deW.
ABSTRACT This study examines the mass distributions and direct and semi‐direct effects of different Anthropogenic Aerosols (AAs) [i.e. sulphate, Black Carbon (BC), Organic Carbon (OC) and all together (SBO)] over South Africa using the 12 year runs of the Regional Climate Model (RegCM4). The maximum burden and Surface Radiative Forcing (SRF) values are found over AA source regions: up to 9 mg m–2 [–12 W m–2] for sulphate and 12.1 mg m–2 [–14 W m–2] for SBO during austral summer, as well as, up to 0.85 mg m–2 [–2 W m–2] for BC and 2.2 mg m–2 [–0.68 W m–2] for OC during austral winter. Contrary to sulphate, both BC and OC aerosols reduce incoming solar radiation reaching the ground via enhancing shortwave radiative heating in the atmosphere. The climatic feedback caused by AAs resulted in changes in background aerosol concentrations. As a result of this and other processes of the climate system, the climatic effects of AAs were also found in remote areas away from the main AA loading zones. However, in terms of statistical significance, the climatic influences of AAs are more prominent in the vicinity of their source regions. The overall feedback of the climate system to the radiative effects of AAs resulted in both positive and negative changes to the Net Atmospheric radiative Heating Rate (NAHR). Areas that experience a reduction in NAHR exhibited an increase in Cloud Cover (CC). During the NAHR enhancement, CC over arid areas decreased; while CC over the wet/semi‐wet regions increased. The changes in Surface Temperature (ST) and sensible heat flux are more closely correlated with the CC change than SRF of AAs. Furthermore, decreases or increases in ST, respectively, lead to reductions or enhancements in boundary layer height and the vice versa in surface pressure. Overall, the results suggest that the feedback of cloud fields has a far‐reaching role in moderating other climatic anomalies.